Relating microclimate, human thermal comfort and health during heat waves: An analysis of heat island mitigation strategies through a case study in an urban outdoor environment. (April 2017) - Salata, Ferdinando; Golasi, Iacopo; Petitti, Davide; de Lieto Vollaro, Emanuele; Coppi, Massimo; de Lieto Vollaro, Andrea
Highlights: Heat waves and human health. Urban microclimate mitigation during the summer. Microclimate simulations of an area located in the center of Rome through ENVI-met V 3.1. Thermal perception analysis through the Mediterranean Outdoor Comfort Index (MOCI). Resilience strategies to the Urban Heat Island (UHI) effect. Abstract: Over the past years the concern of the international scientific community towards the study of the Urban Heat Island (UHI) phenomenon has been growing. Such issue is particularly important in cities as Rome, where it is possible to experience intense heat stress conditions especially when heat waves intensify this phenomenon. Therefore this study wants to examine different mitigation strategies of the urban microclimate by taking into consideration the campus of the Sapienza University of Rome. It was carried out through the software ENVI-met V 3.1 which gave the possibility to reproduce the model of the site (experimentally calibrated) and examine, in terms of MOCI (Mediterranean Outdoor Comfort Index), the different mitigation strategies implemented. This index was also related to the Apparent Temperature and to the health risk. Among the main results provided through this study, it is possible to notice how the solution combining cool roofs, urban vegetation and cool pavement leads, with respect to the current configuration of the site, to a mean and maximum decrease in the MOCI of −2.5 and −3.5. Finally it is able to determine a decrease of about 60% in the health risk for those who are exposed.